One-pot Synthesis of MXene-derived Fe-N-C as Oxygen Reduction Reaction Catalyst in Acidic Medium - Ahmad Junaidi, Norhamizah Hazirah; Wong, Wai Yin; Loh, Kee Shyuan; Choo, Thye Foo; Wong, Jun Yu; Yoon, Li Wan (Bulletin of Chemical Reaction Engineering & Catalysis, 2025)
Fe-N-C is a good candidate as the alternative to the expensive Pt/C catalyst for oxygen reduction reaction (ORR). However, their catalytic activity and durability are still inferior to the Pt/C catalyst. Recently, MXene has emerged as a promising material as the catalyst support for the ORR application due to its good conductivity and mechanical properties. In this work, the MXene-supported Fe-N-C catalyst was synthesized using the one-pot pyrolysis method, in which the MXene was directly added during the preparation of Fe-N-C at various pyrolysis temperatures and mass ratios of Fe salt. The works showed that the one-pot synthesis of Fe-N-C/MXene is ORR active, and has shown improved current density over Fe-N-C with the optimum pyrolysis temperature of 900 °C and mass ratio of 1:1. In addition, the Fe-N-C/MXene also demonstrated superior durability compared to Pt/C.